A Business-Centric Approach to Auditing: Applying the New IPPF Principles. Issue 6 (2nd June 2016) - Zororo, Tichaona
Abstract: Auditing is about adding business value and improving enterprise operations. In order to raise findings beyond tick-the-box and written reports that never get management and the board's attention, auditors need to do more than checklist auditing. They need to understand the business environment, align their audits with strategic, performance and risk objectives of the entity under review, be risk-based, and communicate insights and foresights effectively. Audit findings should be expressed in business terms that relate to organizational crown jewels that are at the hearts of top management and the board of directors. By applying the 10 principles of internal auditing and understanding the business environment, auditors are able to express auditing findings in business language that communicates to key stakeholders, thereby adding value and improving organization operations.